Behaviour of 137Cs in a raised bog in central Sweden - Román Galán, Pilar (SLU/Dept. of Soil Sciences, 2006)
Vertical migration of 137Cs and 137Cs activity concentrations in plants growing on a raised bog in Central Sweden were investigated. Raised bogs are among the most nutrient poor ecosystems. Blocks of soil (peat) and samples of plants were collected from two sites on the bog, the open bog site where no trees were growing and the low pine site with slowly growing Scots pine. The peat at both sites was composed of living Sphagnum mosses in the upper 5 cm layer and dead and more or less decomposed Sphagnum material in deeper layers. Samples were also collected from a forest on mineral soil close to the bog. The soil blocks from the bog were cut in 2 cm layers down to a depth of about 40 cm. The 137Cs activity concentrations (Bq kg-1 dw) in plant samples and the 137Cs activity per m-2 in each peat layer were determined and the migration centers and the migration rates were calculated.